Tanggapan Guru Bahasa Indonesia Terhadap Problem Pembelajaran Sastra dan Upaya Mengatasinya di SMP Kabupaten Sukoharjo - Gunawan, Lukhi Rudy (2016)
This research is a descriptive qualitative study aimed to: (1) identify the problems of Indonesian teachers in teaching literature in junior high school Sukoharjo Regency and (2) describe the response of Indonesian Language teachers in an attempt to overcome the problem of learning literature in junior high school Sukoharjo Regency. The data in this study is the information obtained from the Indonesian Language teachers, while the source of the data in this study is the Indonesian Language teacher in junior high school Sukoharjo Regency. The analysis technique used is the technique of data analysis interactive model. The validity of the data in this study using triangulation sources. The results obtained are: (1) The material of literature is less than the language, (2) only oriented to the text, (3) the allocation of time is less, (4) literary material hasn't been discussed specifically, (5) the portion of material of the language and literature is less balanced, (6) is only theoretical, (7) the books less material, (8) the time limitations in the process of the discussion, (9) students are not interested in the study of literature, (10) the knowledge of literature is limited, (11) low learning motivation , (12) lazy for create their own work, (13) the creativity and interest in reading less, (14) the notion that literature is not important, (15) are hard to stringing the words, (16) the media is limited, (17) facilities and infrastructure is incomplete, (18) the absence of practice exams, (19) in the practice assessment, teacher less the time, (20) the assessment format that has not been uniform. Based on the twentieth these problems then the response of Indonesian Language teachers in an effort to overcome that problems is: (1) adding the material of literature , (2) teaching in accordance with the curriculum, (3) add the allocation of time, (4) add its own material, (5) the addition of servings the material of literature, (6) to change the method of learning, (7) the teacher is more active and creative, (8) if less time, teachers cope with to give the homework to students, (9) students are encouraged to practice practice, (10) by learning literature on an ongoing basis, (12) familiarize more creative, (13) increases interest in reading, (14) changing teaching methods, (15) have the students search for material to his own literature, (16) adding media, (17) teachers seeking on their own, (18) enough written assessment, (19) only provide modest value, and (20) teachers make their own assessment format.